Guarde bem esse sorriso: precariedade e subversão nas obras de Marta Neves - Pedro Henrique Resende Moreira (2023)
This dissertation analyses Marta Neves' artistic work based on the themes of Entkunstung der Kunst, artification, Kitsch and error. Using the writings of Theodor Adorno on the Culture Industry, his concept of Entkunstung, as well as Rodrigo Duarte’s concept of “artification”, we analyse the beginnings of the incorporation of the common object into artistic practices in the 20th century, its relationship with the phenomenon of Kitsch, based on Abraham Moles’ and Umberto Eco’s writings on the subject, and similar manifestations within Brazil’s prior artistic scenes, to assemble a panorama of theoretical and artistic references that support her production. This panorama is then placed in dialogue with our analysis of her works, a survey of her writings and an interview, given for the present dissertation, concluding with a study focused on the series Não Ideias, 2001- current day, to substantiate our reading regarding her appropriation of the object and its relation to the theme of “error”, in an attempt to illuminate her poetics, personal interpretation of Kitsch and her appreciation of everyday life.